NUCLEAR REPROGRAMMING AND ITS EPIGENETIC CONSEQUENCES IN SOMATIC CELL NUCLEAR TRANSFER DERIVED ANIMALS - Meirelles FV (SPERMOVA, 2015)
Somatic cell nuclear transfer (SCNT) is a powerful tool to understand the mechanisms driving the cellular reprogramming, as well as addressing fundamental questions on developmental biology. Hundreds of animals have already been generated through this technology, however its large-scale use is still hampered by the low efficiency and disrupted phenotypes reported in SCNT derived newborns. Therefore, this review aims to expose some of the consequences often seen in cloned animals, as well as to discuss and propose some possibilities and perspectives to avoid epigenetic failures during reprogramming.